Application of FKM Calculation Algorithm for Determination of Degree of Utilization of A Milk Tank Wall (Agricultural Engineering, 2018)
The objective of the paper was to determine the level of circumferential stress in a wall of an open milk tank and to assess the tank wall degree of utilization according to the FKM Guideline calculation algorithm − Analytical Strength Assessment of Components, Made of Steel Cast Iron and Aluminium Materials in Mechanical Engineering. (German: FKM – Forschungskuratorium für Maschinenbau). The stress level in the tank wall was determined based on analytical calculations and numerical method using the FEA – Finite Elements Analysis. Numerical calculations were made in FEMAP with NX NASTRAN Solver (NASTRAN – NASA Structure Analysis). Similar stress values were found using two independent calculation methods. The difference between obtained stress values does not exceed 2%. Based on the FKM algorithm, the safety factor jges = 1.4 and static capacity of the tank wall ask = 19.7% were calculated.